2022
DOI: 10.1371/journal.pone.0263127
|View full text |Cite
|
Sign up to set email alerts
|

Prevalences of SARS-CoV-2 RNA and anti-SARS-CoV-2 among at-risk populations in Chiang Mai and Lamphun provinces, Thailand, during November 2020–January 2021

Abstract: Non-healthcare workers with a high potential for exposure to severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) may contribute to the virus spreading. Data among asymptomatic and high exposure risk populations is still scarce, in particular Chiang Mai and Lamphun provinces, Thailand. We conducted a cross-sectional observational study aiming to assess the prevalence of SARS-CoV-2 RNA positivity, anti-SARS-CoV-2 IgM/IgG, and potential associated factors among asymptomatic/mild symptomatic individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Additionally, the emphasis on the severity of the disease and the impact of COVID-19 infection on their health and life encouraged working adults to adopt appropriate disease prevention behaviors to enable them to continue working [ 19 , 20 ]. Our results also showed that most respondents had a high level of compliance with the DMHTT measures, suggesting that strict adherence to government policies and disease prevention practices is accepted as part of daily life [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 74%
“…Additionally, the emphasis on the severity of the disease and the impact of COVID-19 infection on their health and life encouraged working adults to adopt appropriate disease prevention behaviors to enable them to continue working [ 19 , 20 ]. Our results also showed that most respondents had a high level of compliance with the DMHTT measures, suggesting that strict adherence to government policies and disease prevention practices is accepted as part of daily life [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, vaccinations were an important tool in managing COVID-19, including reducing the cases of severe illness and death, as evidenced by the fact that 76.0% of the study participants had been injected with a COVID-19 vaccine, and that 73.8% intended to be vaccinated against COVID-19 when notified by the public health officials in the places where they were registered. Most of the participants (86.0%) had high compliance with the DMHTT measures, complying with such measures regularly and accepting disease prevention practices as part of their daily lives [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Thailand, serological studies were conducted before the delta wave. A study among non-healthcare workers with a high potential of exposure to SARS-CoV-2 in the northern regions (the Chiang Mai and Lamphun provinces) during the second wave of the outbreak (November 2020-January 2021) reported 0.9% (n = 1651) positive results for antibody tests [10]. Another study in healthcare workers in the Bangkok metropolitan area, and the western and eastern regions of Thailand from January to March 2021 reported that the positive rate for SARS-Cov-2 IgG-spike antibodies was 0.2% (n = 600) [11].…”
Section: Introductionmentioning
confidence: 99%